2017
DOI: 10.3389/fphys.2017.00984
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evaluation of Biocompatibility and Chondrogenic Potential of a Cell-Free Collagen-Based Scaffold

Abstract: Injured articular cartilage has a limited innate regenerative capacity, due to the avascular nature and low cellularity of the tissue itself. Although several approaches have been proposed to repair the joint cartilage, none of them has proven to be effective. The absence of suitable therapeutic options has encouraged tissue-engineering approaches combining specific cell types and biomaterials. In the present work, we have evaluated the potential of a cell-free Collagen I-based scaffold to promote the augmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…This is similar to what was seen in a recent study where cell‐free scaffolds were implanted subcutaneously and cell infiltration improved over time after 4 weeks. [ 49 ] There was clear evidence of collagen type II deposition by infiltrating cells (Figure 6B,E) with more positive (brown) staining evident in the gene‐activated scaffold (Figure 6E). The gene‐free scaffold showed some evidence of collagen type X deposition (Figure 6C), the marker of hypertrophy, with no positive staining present on the gene‐activated scaffold (Figure 6F).…”
Section: Resultsmentioning
confidence: 99%
“…This is similar to what was seen in a recent study where cell‐free scaffolds were implanted subcutaneously and cell infiltration improved over time after 4 weeks. [ 49 ] There was clear evidence of collagen type II deposition by infiltrating cells (Figure 6B,E) with more positive (brown) staining evident in the gene‐activated scaffold (Figure 6E). The gene‐free scaffold showed some evidence of collagen type X deposition (Figure 6C), the marker of hypertrophy, with no positive staining present on the gene‐activated scaffold (Figure 6F).…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, improvements of the physical and structural properties of collagen I-based scaffolds are still required, as stated and highlighted by Irawan et al, in the recently published review [21]. Recently, the biocompatibility and the chondrogenic potential of a new 3D collagen type I-based scaffold has been evaluated by our research group both in vitro and in vivo (etherotopic implantation) [22,23]. Our in vitro results performed using this scaffold in combination with human adipose-tissue derived mesenchymal stem cells (hADMSCs) showed that the scaffold is able to promote the early stages of chondrogenic cell differentiation and that the addiction of specific inductive factors induces complete differentiation as highlighted both by specific cartilage markers expression and typical chondrocyte morphology [22].…”
Section: Introductionmentioning
confidence: 93%
“…The microstructural and morphological properties of the 3D ColI-based scaffold were evaluated by SEM analysis as previously indicated [22,23]. Briefly, Figure 1 shows SEM images of the 3D scaffold at different magnifications, displaying a high porosity of the scaffold with 3D intersected pores without any defined alignment of the collagen fibers.…”
Section: D Scaffold Characterization Before Implantationmentioning
confidence: 99%
“…Calabrese et al in their studies tested a composite bi-layer type-1 collagen-HA/Mg scaffold for osteochondral regeneration, both in vitro and in vivo. They showed that the combination of this scaffold with mesenchymal stem cells (MSC) derived from adipose tissue (hAD-SCs) in the presence of specific differentiation conditions induce osteochondro differentiation both in vitro and in vivo [19][20][21][22][23].…”
Section: Ceramicsmentioning
confidence: 99%